Identifikasi Pola Penggunaan Lahan pada Sektor Perikanan dan Peternakan Berbasis Sistem Informasi Geografis - Auliasari, Karina; Agustine, Thesalonika Nameta (Department of Informatics Engineering, 2016)
Monitoring and evaluation the quantity of the three sectors, agriculture, livestock and fisheries is conducted independently by each local government through the statistics and annual reports. But the development of information fishery and livestock sectors served from annual reports and statistical results have not been able to provide geographic information systems commodities in each district. The results of the development of the geographic information systems indicates that the category feature helps the user to view a visualization mapping fisheries sector and livestock commodities. Based on the visualization mapping analysis results, fisheries sector shows that six of the districts in Barito Utara that has not only a maximum production of fish from the river and three sub-categories of the category of the lake. For the results of visualization mapping livestock sector analysis in cattle category shows that six districts (Lahei, Teweh Tengah, Teweh Timur, Montalat, Gunung Timang and Gunung Purei) is able to fulfill the food needs of beef as a whole districts.